Ricardo flies Ryanair: Strategic human resource management and competitive advantage in a Single European Aviation Market. (3rd August 2020) - Harvey, Geraint; Turnbull, Peter
Abstract: How and why are some firms, such as Ryanair, able to consistently record industry‐leading profitability that sustains a competitive advantage over their rivals? Human resource management (HRM) plays a critical role in four widely recognised profit‐generating mechanisms, albeit not always in ways predicted by mainstream strategic HRM. Studies of HRM → performance grounded in the resource‐based view of the firm invariably focus on the human resources already controlled by the firm—specifically, resources that are rare, inimitable, non‐substitutable and can be exploited through organisation—rather than strategic factor markets where firms acquire their human resources. In doing so, these studies overlook the industrial relations and wider institutional context that might variously promote, permit or preclude particular HR policies and practices. It is only when different profit‐generating mechanisms, either in isolation or combination, are activated under the auspicious conditions of a particular time and place that HRM contributes to sustained competitive advantage.